Relevansi Kurikulum Perguruan Tinggi dalam Perkembangan Dunia Kerja dan Sektor Industri: Kasus Universitas Islam Syekh-Yusuf: The Relevance of the Higher Education Curriculum in the Development of the World of Work and the Industrial Sector: The Case of Universitas Islam Syekh-Yusuf - Joko Rianto; Mustofa Kamil; Walla Astianty Putry; Saepul Bahri (Society, 2022)
This research is driven by developments in the world of work and industry in Indonesia, which absorb fewer university graduates than they need because the graduates do not learn a lot of vocational skill competencies. Developing a higher education curriculum that suits the needs of the industry could address this issue. The gap between higher education and industry manpower needs could be attributed to 1) the absence of a framework that creates an understanding between industry and higher education to develop manpower relevant to industry optimally; 2) the main resource persons are only invited to universities to explain material for a limited period; 3) the facilities and infrastructure in universities do not represent the needs of companies or industries; and 4) the working climate has not yet fully occurred in universities, which are different from what is in the company. This research is an exploratory study that tries to collect and formulate an analysis based on the information collected. The research uses a qualitative approach using case studies and documentation studies. The results of this study indicate that the implementation of the Universitas Islam Syekh-Yusuf curriculum has been going well, following the applicable curriculum preparation regulations. In general, there are several stages in preparing the study program curriculum. These stages are divided into three important stages: the curriculum design stage, the learning design stage, and the learning program evaluation stage. The university has also established partnerships with other companies/organizations in fieldwork practice activities. This supports the development of student experience competencies compared to classroom learning alone. After analyzing the findings in the field with related theories, this research provides suggestions that are expected to be useful for several parties. Universities must find other learning resources for students to be relevant to the company’s needs. Universities need to establish many more partnerships with companies/institutions/organizations to become a place for fieldwork practices for their students so that student competencies will be more developed with a picture of the real job. Education and training are needed for lecturers to develop a curriculum based on applicable regulations that are relevant to global demands. There is a need for further studies to examine the effectiveness of implementing a curriculum based on the business world and the industrial world.